2013
DOI: 10.1002/cbin.10046
|View full text |Cite
|
Sign up to set email alerts
|

PPAR‐γ agonist pioglitazone prevents apoptosis of endothelial progenitor cells from rat bone marrow

Abstract: Selective peroxisome proliferator-activated receptor-γ (PPAR-γ) agonist affects the functions of endothelial progenitor cells (EPCs). This study explores the effect of selective PPAR-γ agonist, pioglitazone, on EPC apoptosis. The cells were cultured and identified via the double staining method in a medium containing different concentrations of pioglitazone. EPC apoptosis was detected by flow cytometry. On Day 7, EPCs engulfed DiL-ac-LDL and FITC-UEA-1, and showed yellow fluorescence in a laser-scanning confoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The positive effect of TZDs on CSC survival with exposure to oxidative agents is consistent with previous studies using other stem cell types [6, 10, 33, 34]. Rosiglitazone treatment protected neuroblasts against apoptosis via upregulation of Bcl-2/Bcl-xl and maintenance of mitochondrial membrane potential under increased H 2 O 2 production induced by hypoxia-reperfusion [33].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The positive effect of TZDs on CSC survival with exposure to oxidative agents is consistent with previous studies using other stem cell types [6, 10, 33, 34]. Rosiglitazone treatment protected neuroblasts against apoptosis via upregulation of Bcl-2/Bcl-xl and maintenance of mitochondrial membrane potential under increased H 2 O 2 production induced by hypoxia-reperfusion [33].…”
Section: Discussionsupporting
confidence: 88%
“…Rosiglitazone treatment protected neuroblasts against apoptosis via upregulation of Bcl-2/Bcl-xl and maintenance of mitochondrial membrane potential under increased H 2 O 2 production induced by hypoxia-reperfusion [33]. In addition, both rosiglitazone and pioglitazone have demonstrated protection of EPCs against apoptosis under oxidative stress [10, 27, 34]. Also of note is that rosiglitazone and pioglitazone restored functional ability of endothelial progenitor cells from type II diabetics to participate in re-endothelialization [5, 23, 26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These discrepancies are mainly due to the strong phenotypic overlap between EPCs and circulating proangiogenic cells from the hematopoietic lineage, a lack of universal data reporting, and—as reported before—differing definitions of the studied cell populations [11]. It was thought that EPCs are present in the bone marrow niche, from where, in response to injury or hypoxia, they are released into the blood and mobilized to the injured tissue [9, 12, 13]. It was originally postulated that, after entering a damaged or ischemic tissue, EPCs stimulate the formation of blood vessels by differentiating into mature endothelial cells (Figure 2).…”
Section: Angiogenesismentioning
confidence: 99%
“…Supporting an anti-inflammatory role of PPAR , Verma and colleagues showed that C-reactive protein-dependent impairment of EPC number and function was ameliorated with rosiglitazone treatment [117]. Furthermore, H 2 O 2 − and TNF -induced apoptosis of EPCs have been shown to be inhibited by pioglitazone and rosiglitazone treatment, respectively [113,118,119]. Consistent with these findings, activation of PPAR has been shown to enhance EPC numbers.…”
Section: Peroxisome Proliferator-activated Receptorsmentioning
confidence: 83%